MILITARY PENAL CODE ON THE CRIMINAL ACT OF INSUBORDINATION COMMITTED BY MEMBERS OF HE MILITARY Decision Number 74-K/PM I-02/AL/VII/2018 - Fadhil Sadam Rusbal (Sean Institute, 2023)
The indonesian army has the main task to protect the sovereignty of the Republic of Indonesia, for this duty, the soldiers are trained and educated to be high discipline, professionals, and obedient to orders from superiors. Being disciplineis not all done by the soldiers, there are still some who commit acts of indisciplinary and contains elements of criminal which example is insubordination. Insubordination is one of the military offense sets in the Code of Military Criminal. The problems examined in this study and its purpose is to determine the criminal proceedings and obtain the data regarding the consideration of the judges in the criminal sanction againts soldiers who commit criminal acts of insubordination in the scope of the Military Court. Based on the problem formulation and the research objective, the research method used in this study is the normative legal research methods, namely legal research conducted by examining the library materials or secondary data related to the Military Law. The study shown that : Firstly, criminal proceedings insubordination was the same case with the handling of military offense in general, that is done through the following stages: the stage of investigation, the submission of the case, the examination at the trial, and the verdict. Secondly, one consideration of the judges in giving judgment in insubordination case, for instance, is whether the perpetrator was ever awarded in his career as military personnel.